MONEY POLITIK PADA KEPEMILUAN DI INDONESIA - M Eza Helyatha Begouvic; Bayu Cuan (SOL JUSTICIA, 2021)
Abstract: Money politics is the biggest scourge in every political recruitment, including in regional head elections (pilkada). Through the elections, it is hoped that qualified regional leaders will be elected in accordance with the will of the people, but in its implementation, one of the "democracy parties" is exhibiting fraudulent behavior, dishonesty, lies in the campaign and even fooling the public by giving money or goods before the election so that voters choose certain candidates known as money politics (money politics). The approach in this research is the Juridical Empirical approach. This research will be conducted in Palembang City, South Sumatra Province, which is the object and main focus of researchers in viewing and analyzing Money Politics in Elections in Indonesia. Keywords : Money Politic, Election , and Law Enforcement.